The Neverlands of Nature : Exploring Representations of the Non-Human in Visitor Information Publication Material on Swedish National Parks - Fälton, Emelie; Hedrén, Johan (Linköpings universitet, Tema Miljöförändring, 2020)
In this paper, we distinguish, make visible, and problematize how thenon-human world (often depicted as nature) in Swedish national parks comes into beingthrough representations in visitor information publications, and what the productiveeffects of those representations are. Through a discursive analysis, we identify seven discursiveformations that concern portrayals of the non-human world. On the one hand,it is represented as extraordinary and sublime pieces of wild and pristine nature—and onthe other, as ordinary and accessible. Despite this divergence, these kinds of spaces functionas national heritage with an elitist status, which creates hierarchizations betweennational parks and other spaces, but also between the national parks themselves. Northand south are assigned different attraction values and portrayed as desirable in differentcontexts. The north is wild, pristine, and sublime, while the south is safe, available, andalways open to tourists. Furthermore, the material generates portrayals of national parksas places for learning, where the non-human world is displayed, explored, experienced,and taught. The uniting force of these formations is the focus of national parks as placesof otherness, which turns them into heterotopian neverlands far away from the mainlandof modernity.